Fertility decisions and alternative types of childcare - Chiara Pronzato (IZA World of Labor, 2017)
Increasing population age and low fertility rates, which characterize most modern societies, compromise the balance between people who can participate in the labor market and people who need care. This is a demographic and social issue that is likely to grow in importance for future generations. It is therefore crucial to understand what factors can positively influence fertility decisions. Policies related to the availability and costs of different kinds of childcare (e.g. formal care, grandparents, childminders) should be considered and promoted after an evaluation of their effects on the probability of women having children.
Keywords: 330; formal childcare; grandparents; childminders; fertility; work